Effect of residue incorporation and INM on productivity of spring maize (Zea mays) in rice (Oryza sativa)-based cropping system - SAHOO, PRIYANKA; SINGH, THAKAR; SAINI, KULVIR SINGH; KAUR, JAGMOHAN (The Indian Journal of Agricultural Sciences, 2024)
A field experiment was conducted during 2019 and 2020 at the research farm of Punjab Agricultural University, Ludhiana, Punjab to study the effect of integrated nutrient management (INM) on grain yield, economics, and system productivity of spring maize (Zea mays L.) under residue incorporation in a diversified cropping system. The main plot consisted of 4 treatment combinations, viz. straw removal + 100% NPK + farmyard manure (FYM) @50 t/ha; straw removal + 150% NPK; straw incorporation + 100% NPK + FYM @50 t/ha; and straw incorporation + 150% NPK, while sub-plot consisted of 3 nutrient levels (75%, 100% and 125% NPK) applied to spring maize planted in a single row and double rows on bed. The results revealed that combined application of straw incorporation + 100% NPK + FYM @50 t/ha resulted in significantly higher grain yield (80.1 and 83.6 q/ha), net returns (259.9 and 300.2 ×103 ₹/ha), benefit cost ratio (1.34 and 1.51) and system productivity (82.9 and 89.1 kg/ha/day) of spring maize and application of 125% NPK to double row on bed resulted in significantly higher grain yield (14.6%, 12.9%) and system productivity (5.4%, 4.7%) as compared to 100% NPK to single row on bed during 2019 and 2020, respectively. Residue incorporation along with INM increased grain yield, net returns, nutrient uptake and system productivity of spring maize.